Unraveling gene expression and physio-biochemical responses in citrus species under water stress and water recovery conditions - Nirmala Friyanti Devy; Hardiyanto; Farida Yulianti; Agus Sugiyatno; Ismon Lenin; Emi Budiarti; Anang Triwiratno; Mutia Erti Dwiastuti; Baswarsiati; Sri Widyaningsih; Chaireni Martasari (Journal of Agriculture and Food Research)
In Indonesia, many citrus trees are planted in marginal areas reliant solely on erratic rainfall, leading to suboptimal fruit production and quality. Meanwhile, studies on the response of gene expression and physio-biochemical traits in citrus seedlings derived from different species to water stress are limited. This study aims to fill that gap, exploring how drought and water recovery treatments affect citrus species. This study employed a factorial randomized block design with two factors: drought stress as the first factor and cultivar consisting of one-and-a-half-year-old Mandarin (Citrus reticulata Blanco. cv. Keprok Batu 55/K) and Tangerine (Citrus nobilis I. cv. Siam Banjar/S), as the second factor, each with three replications. The drought treatments were as follows: control, watering once a week (P1); drought stress for 13 days; water recovery for 39 days (P2); drought stress for 26 days; water recovery for 26 days (P3); P4: drought stress for 39 days; water recovery for 13 days (P4); and drought stress for 52 days (P5). Significant upregulation of drought-responsive genes such as ACS, ETR1, PIP1, PIP2, CsNF-YA5, and CHLASE was observed, particularly in the S cultivar following prolonged water deficit. The S also had a higher response than the K to the expression of genes related to flowering, such as Cs-LFY, Cs-AP1, and Cs-SL1. A significant interaction was detected on Chl-a (P5-K), Chl-b (P5-K), carotenoids (P5-K and P5-S), proline (P4-S), and TSS (P4-S). Based on gene expression, proline, TSS, flowering, and fruiting, this study suggests that the S cultivar is more tolerant than the K cultivar.